Spreading positive change: Societal benefits of meditation - Engert, Veronika; Klimecki, Olga Maria; Kanske, Philipp; , the Mindful Universities Research Group (Frontiers in Psychiatry, 2023)
Research over the past decades has revealed a variety of beneficial effects of meditation training. These beneficial effects span the levels of health and well-being, cognition, emotion, and social behavior. Around the same time, sociologists have shown that traits and outcomes on the individual level have the potential to spread in communities over three or more degrees. This means, for example, that changes can spread from one person to the next, and on to yet another person. Here, we propose that meditation-induced changes may likewise spread through the social networks of meditation practitioners. Such spreading may happen by positively influencing others through prosocial actions, improved cognitive functioning, and increased positive affect. Positive affective states and their underlying physiological correlates may also be shared in the literal sense. We argue that the spreading of positive meditation effects could provide the basis for collective responses to some of the urgent challenges we face in our current time and society, and call for future meditation research to examine the phenomenon.